Reporte de caso: enteropexia en intususcepción recurrente en golden retriever cachorro (2022)
Intussusceptions are defined as the invagination of a segment into the lumen to the adjacent segment in a peristaltic direction or occasionally in a retrograde direction. The main clinical signs are vomiting, anorexia, lethargy and abdominal pain. These may be associated with infectious and non-infectious causes; and its highest incidence occurs in breeds such as Labrador, Mestizo, German Shepherd, Golden Retriever and German Shorthaired Pointer, especially in individuals under one year of age. The diagnosis of the disease can be made through a general clinical examination, based on clinical signs and abdominal palpation; although abdominal ultrasonography is especially indicated. Treatment is surgical and consists of manual reduction or bowel resection and anastomosis depending on the severity of the condition. Although recurrence is not common, there are reports and the indicated treatment is enteropexy or enteroplication. This report evidences the surgical management given to a recurrent intussusception in a Golden Retriever puppy. The patient presented parasitosis due to oocysts of Cystoisospora spp, which triggered an intussusception at the level of the jejunum that was resolved by manual reduction and 12 hours later it presented again in another portion of the jejunum, for which an enteropexy was performed, allowing the intussusception to be resolved and preventing recurrence again. The objective of this case report is to describe the surgical techniques used to resolve recurrent intussusceptions and the possibility of prophylactic use of enteropexy or enteroplication as a preventive measure for their recurrence.